Does inflation change when countries adopt inflation targeting? - Winkelried, Diego (2005)
This paper analyses the evidence about the impact of adopting inflation targeting (IT) on inflation dynamics in a wide range of countries. ln particular, it reports on the econometric evaluation undertaken by Vega and Winkelried (200S) and compares this with results from other authors. In general, our comparative exercise shows that the impact of adopting inflation targeting over mean inflation is moderate in developed countries, but that its effects are significant when adopted by less-developed countries.